PENGARUH VARIASI ROTASI TUBUH TERHADAP INFORMASI ANATOMI PADA PEMERIKSAAN RADIOGRAFI SHOULDER JOINT METODE SCAPULAR Y VIEW - Agustina Dwi Prastanti; Ardi Soesilo Wibowo; Rovikhotus Sa'idah (Jurnal Imejing Diagnostik (JImeD), 2019)
Background: Shoulder joint examination of the scapular "Y" method in one hospital uses a body rotation of 350 – 450 whereas in theory the position of the patient's body is rotated so mid coronal plane (MCP) forms an angle of 450 – 600 to the image receptor (IR). Therefore it is necessary to conduct research to obtain optimal anatomy information of shoulder joint. The purpose of this research is to know the information of shoulder joint anatomy and to know the optimal body rotation in showing the anatomy information of shoulder joint.Methods: The type of research is experimental research with descriptive approach. Methods of data collection conducted by experiment and observation. This research conducted with phantom thorax which was exposed six times, same exposure factor and the variation body rotation 350, 400, 450, 500, 550, 600 and complete questioner. The questionnaire was completed by three radiologists. Scoring results of the respondents are processed and presented in the tables and graphs to be described and analyzed.Results: The results examination shoulder joint with scapular "Y" method is a different assessment variation on each shoulder joint anatomy information, distortion on the radiographs, and the optimal rotation of the body is a rotation of 550 to IR. This refers theory from Frank, Long, and Smith (2012) that the clinical indication of suspected dislocation shoulder joint scapular "Y" method uses the patient standing upright and the position of the body object is rotated so that the MCP of the body forms an angle of 450-600 to IR.Conclusion: The radiographic technique of the AP projection pedis with a variation of 350, 400, 450, 500, 550, 600 produces different anatomical information. There are distortions and differences in anatomical information which includes the location of the coracoid process under the clavicula, humeral head superposition with glenoid cavity, body of scapula free from ribs, acromion projected laterally and not superposition, medial border scapula superposition with lateral border scapula. The greater the body's rotation towards IR, the greater the distortion that occurs. The optimal angle in generating anatomical information on the scapular “Y” view method examination is 50 º that very useful to evaluate dislocation of shoulder joint.